2010
DOI: 10.1111/j.1600-0714.2010.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of human papilloma virus, herpes simplex virus and Epstein-Barr virus DNA in oral biopsies from Sudanese patients with regard to toombak use

Abstract: Using PCR/DNA sequencing, we investigated the prevalence of human papillomavirus (HPV), herpes simplex virus (HSV) and Epstein-Barr virus (EBV) DNA in brush biopsies obtained from 150 users of Sudanese snuff (toombak) and 25 non-users of toombak in formalin-fixed paraffin-embedded tissue samples obtained from 31 patients with oral dysplasias (25 toombak users and 6 non-users), and from 217 patients with oral cancers (145 toombak users and 72 non-users). In the brush tissue samples from toombak users, HPV was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 28 publications
4
66
2
2
Order By: Relevance
“…Speculation on the increasing role of HPV in oropharyngeal cancer in Africa is abundant, particularly in settings where HIV is highly prevalent and where HIV-infected individuals may have increased acquisition and persistence of oncogenic HPV strains at multiple anatomic sites. 51,52 Yet active HPV replicative infection has not been well described in HNSCC (and oral cancer) in sub-Saharan Africa except for the 2010 study by Jalouli et al 29 who showed that 25% of 217 oropharyngeal/oral cavity squamous cell carcinoma specimens in Sudan were positive for HPV. HPV positivity was reported by anatomic subsite, but clear anatomic trends were not described and oropharynx sites were not exactly identified.…”
Section: Hiv/aids Hpv and Oral Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Speculation on the increasing role of HPV in oropharyngeal cancer in Africa is abundant, particularly in settings where HIV is highly prevalent and where HIV-infected individuals may have increased acquisition and persistence of oncogenic HPV strains at multiple anatomic sites. 51,52 Yet active HPV replicative infection has not been well described in HNSCC (and oral cancer) in sub-Saharan Africa except for the 2010 study by Jalouli et al 29 who showed that 25% of 217 oropharyngeal/oral cavity squamous cell carcinoma specimens in Sudan were positive for HPV. HPV positivity was reported by anatomic subsite, but clear anatomic trends were not described and oropharynx sites were not exactly identified.…”
Section: Hiv/aids Hpv and Oral Cancermentioning
confidence: 99%
“…Toombak is a product of fermented and cured tobacco containing sodium bicarbonate placed in the labial sulcus and predominantly consumed in Sudan and southern Saudi Arabia. 28,29 It is heavily contaminated with microorganisms which likely contribute to carcinogenesis. 30 Khat is a psychoactive stimulant derived from the leaves of the Catha edulis plant, which is a flowering evergreen shrub indigenous to East Africa and parts of the Middle East.…”
Section: Aetiology and Risk Factors Of Oral Cancer In Africamentioning
confidence: 99%
“…A number of studies point to the co-infection by HPV and EBV in cervix cancer (Szkaradkiewicz et al, 2004) and in oral squamous cell carcinoma (Al Mustafa et al, 2009;Achayra et al, 2014;Jiang et al, 2015). Several articles indicate that co-infection by multiple oncogenic viruses may be an important risk factor in the development of OSCC (Jalouli et al, 2011;Achayra et al, 2014;Jiang et al, 2014;. Al Moustafa et al (2009) showed that high-risk HPV and EBV co-infections play an important role in initiating neoplastic transformation of human oral epithelial cells.…”
mentioning
confidence: 99%
“…Helicobacter pylori was found in 80% of patients with gastritis, 56% of patients with duodenal ulcer, 60% of patients with duodenitis and 16% of normal control subjects (Azim et al, 1994). The role of HPV, herpes simplex virus and Epstein-Barr virus in the etiology of oral cancers (Ahmed and Eltom, 2010;Jalouli et al, 2010), as well as the role of HPV in the development of cervical cancers cancer (Salih et al, 2010;Elasbali, et al, 2012;Ginawi et al, 2012) in different parts of Sudan was well established.…”
Section: Figure 2 Description Of the Study Subjects Answered (No) Inmentioning
confidence: 99%